Application of Coping Strategy on Victims of Physical and Verbal Violence in Dating Relationships to Overcome Psychological Disorders in Adolescent Females in Makassar City - Imayah, Husnun; Syria; Nasir, Sudirman; Riskiyani, Shanty; Maria, Ida Leida (Journal of Neonatal Surgery, 2025)
Background: Dating violence (DV) is a social phenomenon that often affects teenagers, especially girls. Objective: This study aims to describe the forms of physical and verbal violence experienced by adolescent girls and the coping strategies used to overcome the psychological impact of this violence. Method: This study uses a descriptive qualitative approach with an in-depth interview method with 15 informants from various universities in Makassar City. Results: The results of the study showed that victims experienced various forms of violence such as being hit, slapped, shouted at, and insulted, which resulted in the emergence of psychological disorders such as anxiety, trauma, depression, and low self- esteem. Coping strategies used include Emotion Focused Coping (EFC) such as escape- avoidance and positive reappraisal, and Problem Focused Coping (PFC) such as seeking social support and confrontive coping. Conclusion: This study emphasizes the importance of psychological counseling and social support in helping adolescent girls cope with the impact of dating violence